Estudio de la enseñanza-aprendizaje de las cuatro operaciones básicas de matemática : estudio de caso en quinto año de Educación General Básica en la Escuela Abelardo Páez Torrez de la ciudad de Ibarra - Castro Amaguaña, Mayra Isabel (2018)
The present case analysis describes, "The teaching of the four basic operations of mathematics in the fifth year of basic education, of the Abelardo Páez Torres school", since it has been demonstrated according to diagnoses that there are difficulties on the part of the children in the learning mathematical operations. This study was carried out to express the contexts that take place in the classroom, the process that evidences the difficulties that fifth-year children have, the methodology that the teacher uses according to the teaching-learning process of mathematical operations. To carry out this study, the qualitative method was used with the help of methodological instruments, such as observation, interview, and field diary and observation sheets of the practical classes, which provided the necessary information for the respective description. The technique used for this purpose was field observation in the educational institution. The results that stand out most in this study are: the teacher carries out the activities based on a plan, but lacks didactic strategies that motivate the child in his learning through experiences and using better materials that are around him; there is no evidence of the use of a methodology for the construction of knowledge, to foster interest or curiosity on the part of children in the development of teaching and learning, because there is no connection with the activities of daily life.